An integrated multifocal tDCS-EEG protocol for reducing cognitive and affective symptoms in mild cognitive impairment and early stages of dementia: a crossover double-blind randomized controlled trial - Laura Catalano; Laura Sagliano; Anna Visciglio; Pasquale Russo; Stefania Miniello; Luigi Trojano; Francesco Panico (Frontiers in Neurology)
BackgroundAvailable evidence on effectiveness of non-pharmacological interventions for cognitive and affective symptoms in Mild Cognitive Impairment (MCI) and the early stages of dementia is encouraging but still limited. Multifocal high-definition brain stimulation could detain the potential of improving these symptoms by modulating the activity of a fronto-temporal network. Moreover, combined electrophysiological measures might contribute monitoring the underlying neurophysiological effects. In this study protocol an innovative and integrated intervention for patients with MCI and early-stage dementia will be proposed, also exploring the modulatory role of some specific variables such as education and cognitive reserve.MethodSixty patients with MCI and early-stage dementia will be enrolled in a crossover double-blind randomized controlled trial utilizing an integrated intervention combining conventional cognitive treatment with multifocal brain stimulation and electrophysiological recordings. A battery of standardized neuropsychological tests will be employed at several time points to monitor changes, and inferential statistics will identify the changes specifically associated with the intervention. Regression analyses will be performed to ascertain the extent to which education and cognitive reserve scores may influence intervention outcomes. Analysis of electrophysiological data will contribute characterizing responders to treatment.DiscussionThe project will contribute to a transformation in the landscape of non-pharmacological interventions for MCI and dementia, integrating diverse techniques and levels of analysis within a unified, comprehensive approach.Trial registrationThis study is registered at ClinicalTrials.gov database under registry number NCT06668610 on October 30, 2024.